Réponses

  • Utilisateur Brainly
2013-05-29T14:26:04+02:00

2x+3y=13 et -x-4y=21

donc 2x+3y=13 et -2x-8y=42

donc par somme -5y=55 donc y=-11

 

donc -x+44=21

donc -x=-23 donc x=23

 

donc S={(23;-11)}

Meilleure réponse !
  • carys
  • Modératrice confirmée
2013-05-29T14:30:18+02:00

tu as le système 

2x+3y=13

-x-4y=21

 

Donc

-2x - 3y = -13

-2x - 8y = 42

 

-2x - 3y - (-2x - 8y) = -13 - 42
-2x - 3y + 2x + 8y = -55

-3y + 8y = -55

5y = -55

y = -55/5

y = -11

 

2x + 3y = 13

2x + 3*(-11) = 13

2x - 33 = 13

2x = 46

x = 46/2

x = 23

 

voilà :)